PTU-089 National study of outcomes for cholangiocarcinoma patients following biliary endoscopy: linkage analysis of administrative data for English hospitals (2006–2008). (28th May 2012) - Polavarapu, N; Bowering, K; Thompson, E; Sturgess, R; Pearson, M; Bodger, K
Abstract : Introduction: Cholangiocarcinoma (CC) is a rare and challenging cancer with poor prognosis and low operative rate. Early successful biliary drainage is a key determinant of outcome and ERCP is the primary modality. It is unclear whether current care organisation for CC is optimal. We report a national study aimed at describing outcomes for all patients undergoing ERCP for CC in English hospitals and volumes at cancer networks and institutions. Methods: We built on linkage methods applied to overall ERCP mortality 1 to develop new techniques to map the entire pathway of hospital care for incident cases of CC. 2 years of Hospital Episode Statistics (HES) data were merged (2006–2008) and admissions screened for CC diagnosis. To identify a 1-year incident cohort of CC, we selected only patients with first cancer coding in middle year (October–September), then extracted all admissions within 6 months (before and after) of first cancer coding, ordered chronologically, screened for ERCP, radiological intervention (PTC) and major surgery codes. Identified first and subsequent procedure dates, admission diagnoses and co-morbidity. Linkage to death registry for death date. Cases allocated to cancer networks using provider codes. Results: Nationally, 1211 CC patients underwent ERCP with mean age (SD) of 72 (12) years and 623 male (51.4% ). First ERCP was performed during an acute (emergency ) hospitalisation in 690 cases (57%). ERCP case volumes for CC ranged from 7 to 79 patients per Cancer Network and 1–57 patients per Trust (n=146 institutions). Outcomes (post-first ERCP): Mortality : 7 day [40 (3.3% )]; 30 day: 172 (14.2% ); 365 day: 781 (64.5% ). Emergency readmission : 7 day: 110 (9.1% ); 30 day: 252 (20.8% ). Additional PTC : 213 (17.6% ) with poorer 365 d survival in those needing both (ERCP alone: 64.5% vs ERCP+PTC: 73%, p=0.013, non-surgical cases only). Patients requiring first ERCP during an acute hospitalisation had poorer prognosis than those on elective pathway (Log rank, p<0.001). 365 day mortality for surgical 42.4% vs non-surgical 66.2% (p<0.001). Conclusion: First endoscopic intervention for this rare form of cancer is undertaken in most English hospitals, often during acute hospitalisation. There is wide variation in institutional case load. These data provide a potential tool for exploring variation in relation to local or network service provision and organisation. Competing interests: None declared. Reference: 1. Bodger K, Bowering K, Sarkar S, et al. All-cause mortality after first ERCP in England: clinically guided analysis of hospital episode statistics with linkage to registry of death. Gastrointest Endosc 2011;74 :825–33.